Risk factors and clinical outcomes of severe postoperative hypoxaemia following surgical repair of Stanford type A aortic dissection: a retrospective cohort study - Lin, Min; Xiang, Yuping; Luo, Tianhui; Zeng, Ling; Fan, Jingxiu (Frontiers in Medicine, 2025)
ObjectiveThis study aimed to investigate independent risk factors of severe postoperative hypoxaemia in patients with type A aortic dissection (TAAD), for providing a reference for clinical healthcare professionals to identify high-risk patients early and formulate postoperative severe hypoxaemia prevention and intervention plans.MethodsThis was a retrospective, observational study, patients with Stanford TAAD who underwent aortic surgery (n = 755) between March 2021 and July 2024 were enrolled. Relevant preoperative and intraoperative clinical data were collected. Univariate and logistic regression analyses were used to identify risk factors of severe hypoxaemia after TAAD.ResultsOf the 755 patients with postoperative TAAD, 192 (25.43%) experienced severe postoperative hypoxaemia. Multivariable logistic regression analysis revealed body mass index (BMI) (odds ratio [OR] = 1.137), white blood cell count (WBC) (OR = 1.068), hypertension (OR = 2.693), chronic kidney disease (CKD) (OR = 2.767), highest lactate level (OR = 1.094) as independent predictors of severe postoperative hypoxaemia. Femoral artery cannulation (OR = 0.533) was a protective factor against severe postoperative hypoxaemia. Severe hypoxaemia increased hospitalization costs, prolonged mechanical ventilation duration, and extended intensive care unit and hospital stay durations.ConclusionThe high severe hypoxaemia prevalence after TAAD is associated with poor clinical outcomes. Preoperative BMI, WBC, hypertension, CKD and intraoperative highest lactate level were risk factors for severe postoperative hypoxaemia. Clinical healthcare professionals should closely monitor high-risk patients, intensify oxygenation index surveillance, and intervene promptly to minimize hypoxaemia and improve patient prognosis.